ROLE OF ORAL MIDAZOLAM AS A PROCEDURAL SEDATIVE IN CHILDREN AGED 6 MONTHS TO 12 YEARS - ABHISHEK K PHADKE; PRAMEELA JOJI; SANDEEP KUMAR (International Journal of Pharma and Bio Sciences, 2014)
Pediatric procedural sedation is a safe, effective and humane way to facilitate appropriate medical care. We conducted a prospective, open-label randomized controlled trial in 272 children in the age group of 6 months to 12 years who need to undergo a procedure requiring pain or anxiety management. The objective was to evaluate the efficacy and safety profile of oral midazolam in comparison with intravenous midazolam. Out of 272 children, 42.5% children underwent invasive procedures and the rest non-invasive. For non-invasive procedures, 79% subjects in the oral group were adequately sedated, compared to 63% in the intravenous group. For invasive procedures, 71% subjects were adequately sedated with oral midazolam and 78% in intravenous group. 85% procedures were successfully completed in oral group compared to 79% in intravenous. Occurrence of adverse effects like desaturation, apnea and paradoxical hyper agitation was less with oral midazolam compared to intravenous.